Study the release of urea from Agrium® coated urea using UV-Vis spectrometer - Trinh, T.H. (Trans Tech Publications Ltd, 2014)
Elucidating the release pattern of controlled release fertilizer (CRF) is important not just for manufactures but also for farmers because it assists them in making judgments of fertilizer effectiveness and nutrient planning. Investigation on the release pattern of different types of CRF both in the laboratory and in the crop-field is crucial in order to determine the effectiveness of fertilizer on plant growth. Consequently, the fertilizer application could be planned to meet the crop requirement. This paper presents a practical approach to analyze the release pattern using Agrium® coated urea. UV-Vis spectrometer is employed to analyze the amount of nitrogen released. The approach reduced analytical error by preventing sample dilution before measuring. According to laboratory results, UV-Vis spectrometer has shown a good potential to be used in studying the nutrient release behavior from CRF. A sigmoidal shape has been obtained from the release profile, and is corresponded with findings in other studies. The results satisfy the criteria for CRF specified by European Committee for Standardization. Collectively, this study demonstrated that the UV-Vis spectrometer is a promising equipment, which can be utilized in studying controlled release behavior. © 2014 Trans Tech Publications, Switzerland.